2016
DOI: 10.15184/aqy.2015.176
|View full text |Cite
|
Sign up to set email alerts
|

Migrations and interactions in prehistoric Beringia: the evolution of Yakutian lithic technology

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 21 publications
2
14
0
1
Order By: Relevance
“…From the perspective of archaeology, the transition to stone technology in Northeast Asia provides clues as to the demographic history of this region. Remains of microblade technology are extremely rare in sites of the Dyuktai culture (35–13 kya), which is the earliest culture identified by archaeology in Northeast Asia (Gómez Coutouly, 2016; Vasil'ev et al, 2002; Yi et al, 1985). The Dyuktai culture was replaced by the Sumnagin culture (10.5–6 kya), which left remains indicating flourishing microblade technology, which diffused from low latitude regions of northern Asia (Goebel, 2002; Gómez Coutouly, 2016; Pitul'ko, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of archaeology, the transition to stone technology in Northeast Asia provides clues as to the demographic history of this region. Remains of microblade technology are extremely rare in sites of the Dyuktai culture (35–13 kya), which is the earliest culture identified by archaeology in Northeast Asia (Gómez Coutouly, 2016; Vasil'ev et al, 2002; Yi et al, 1985). The Dyuktai culture was replaced by the Sumnagin culture (10.5–6 kya), which left remains indicating flourishing microblade technology, which diffused from low latitude regions of northern Asia (Goebel, 2002; Gómez Coutouly, 2016; Pitul'ko, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Remains of microblade technology are extremely rare in sites of the Dyuktai culture (35–13 kya), which is the earliest culture identified by archaeology in Northeast Asia (Gómez Coutouly, 2016; Vasil'ev et al, 2002; Yi et al, 1985). The Dyuktai culture was replaced by the Sumnagin culture (10.5–6 kya), which left remains indicating flourishing microblade technology, which diffused from low latitude regions of northern Asia (Goebel, 2002; Gómez Coutouly, 2016; Pitul'ko, 2001). Archaeologists have suggested that ancient populations of the Dyuktai culture migrated to North America in an earlier age, while ancient populations with microblade technology entered North America later (Gómez Coutouly, 2016, 2018; Yi et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the production of microblades and blades has been attributed to pressure knapping in diverse geographic and chronological contexts worldwide, such as France (Binder 1984), Greece (Perlès 1984), Denmark (Callahan 1985), Turkey (Binder and Balkan-Atlı 2001), the Canadian Arctic (Desrosiers and Sørensen 2012) and central Asia (Brunet 2002). Pressure knapping to produce microblades was first identified in Siberia by Flenniken (1987) and has since been suggested for most of the Paleolithic microblade assemblages from Northeast Asia and North America (Kobayashi 1970; Morlan 1976; Inizan et al 1992; Tabarev 1997, 2012; Inizan et al 1999; Derevianko and Kononenko 2003; Gryba 2006; Gómez Coutouly 2007, 2011a, 2011b, 2012, 2015, 2016; Takakura 2012; Gómez Coutouly and Ponkratova 2016).…”
Section: Pressure Knapping Of Microbladesmentioning
confidence: 99%
“…Different techniques (called “modes”) for the removal of blades and microblades by pressure knapping have been proposed by authors such as Pelegrin (Pelegrin 1988, 2003, 2012; Gómez Coutouly 2011a) to reproduce various archaeological cases, which vary widely in size, from small microblades to very large blades. But in the chrono-cultural context under discussion, only pressure microblades have been recognized, blade pressure knapping being a Holocene phenomenon (Gómez Coutouly 2011b, 2016).…”
Section: Pressure Knapping Of Microbladesmentioning
confidence: 99%
“…Thirteen cultural components (3A–9) belong to the Late Upper Palaeolithic and are associated with the Dyuktai Culture of Yakutia and adjacent regions. The ‘trademark’ of this complex is the microblade technology, and microblades were produced at the Bol’shoy Yakor’ I by the Yubetsu method (see Kuzmin et al 2007: 53–78, 125–46; Gómez Coutouly 2016). About 30 wedge-shaped cores and around 1700 microblades were recovered; refitting was undertaken to reconstruct the technological steps.…”
mentioning
confidence: 99%